MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SD PADA MATERI BANGUN DATAR DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL): Penelitian Tindakan Kelas Menggunakan Model Problem Based Learning (PBL) - Sri Rahayu Puji Lestari; Geri Syahril Sidik; Winarti Dwi Febriani (STKIP Subang, 2025)
This study aims to improve the learning motivation of fifth grade students of SDN 1 Sukamanah in learning mathematics on the material of flat shapes (squares, rectangles, and triangles) by applying the Problem Based Learning (PBL) learning model. This study is a Classroom Action Research (CAR) consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 23 fifth grade students of SDN 1 Sukamanah consisting of 12 female students and 11 male students. Data collection methods through observation, questionnaires, and documentation. Based on the results of data analysis in cycle I, the average student learning motivation was 64.5%, including the moderate category, and in cycle II the average student learning motivation was 87.4%, including the very high category. From the results of the study, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve student learning motivation on the material of flat shapes (squares, rectangles, and triangles).